Evolutionary Dynamics of Structural Variation at a Key Locus for Color Pattern Diversification in Cichlid Fishes. (10th December 2019) - Kratochwil, Claudius F; Liang, Yipeng; Urban, Sabine; Torres-Dowdall, Julián; Meyer, Axel
Abstract: Color patterns in African cichlid fishes vary spectacularly. Although phylogenetic analysis showed already 30 years ago that many color patterns evolved repeatedly in these adaptive radiations, only recently have we begun to understand the genomic basis of color variation. Horizontal stripe patterns evolved and were lost several times independently across the adaptive radiations of Lake Victoria, Malawi, and Tanganyika and regulatory evolution of agouti - related peptide 2 ( agrp2/asip2b ) has been linked to this phenotypically labile trait. Here, we asked whether the agrp2 locus exhibits particular characteristics that facilitate divergence in color patterns. Based on comparative genomic analyses, we discovered several recent duplications, insertions, and deletions. Interestingly, one of these events resulted in a tandem duplication of the last exon of agrp2 . The duplication likely precedes the East African radiations that started 8–12 Ma, is not fixed within any of the radiations, and is found to vary even within some species. Moreover, we also observed variation in copy number (two to five copies) and secondary loss of the duplication, illustrating a surprising dynamic at this locus that possibly promoted functional divergence of agrp2 . Our work suggests that such instances of exon duplications are a neglected mechanism potentially involved in the repeated evolution and diversification that deserves more attention.